2011
DOI: 10.1177/1938640010397657
|View full text |Cite|
|
Sign up to set email alerts
|

Bilateral Simultaneous Achilles Tendon Rupture in the Absence of Risk Factors

Abstract: Therapeutic, Level IV, retrospective case study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Aşil tendon rüptürleri sıklıkla, yaş ile beraber kanlanmanın zayıfladığı tendonun kalkaneusa yapışma yerinden 2-6 cm proksimalden olmaktadır. (8,9) Aşil tendon rüptürlerinin %1 den azının bilateral olduğu ve risk faktörü olmaksızın rüptürlerin daha nadir olduğu bildirilmektedir (10). Tendon rüptürleri birçok faktöre bağlı olabilmekle beraber spontan rüptürlerin etyolojisi henüz aydınlatılabilmiş değildir (10) (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aşil tendon rüptürleri sıklıkla, yaş ile beraber kanlanmanın zayıfladığı tendonun kalkaneusa yapışma yerinden 2-6 cm proksimalden olmaktadır. (8,9) Aşil tendon rüptürlerinin %1 den azının bilateral olduğu ve risk faktörü olmaksızın rüptürlerin daha nadir olduğu bildirilmektedir (10). Tendon rüptürleri birçok faktöre bağlı olabilmekle beraber spontan rüptürlerin etyolojisi henüz aydınlatılabilmiş değildir (10) (12).…”
Section: Discussionunclassified
“…Aşil tendon rüptürleri konservatif ve cerrahi olarak tedavi edilebilmektedir. Bilateral rüptürlerde cerrahi tedavi ön plana çıkmakla birlikte konservatif tedavi edilmiş bilateral rüptür olguları bildirilmiştir (10). Konservatif tedavi cerrahi tedaviye göre daha fazla yeniden rüptür oranına sahiptir.…”
Section: Discussionunclassified
“…Achilles tendon is the most frequently ruptured tendon in the lower extremity and it is usually seen at the active individual men at their fourth or fifth decade of life. Male-female rate is altering between 2/1 and 12/1 [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Coexistent rheumatological diseases or endocrinopathies, chronical overuse, fluoroquinolone consumption are well defined etiologic factors at spontaneous achilles tendon rupture however the mechanism of underlying tendon degeneration was also described [4]. Besides these factors, Rao et al reported a 38-year-old woman who had bilateral spontaneous achilles tendon rupture and they proposed that it was associated with hypotyroidism [5]. In some studies correlation with hypercholesterolaemia [6,7], hyperparatyroidism and renal failure [8,9] has been exhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation